2006
DOI: 10.1016/j.joca.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of zonal articular chondrocytes measured by atomic force microscopy

Abstract: Our findings suggest that chondrocyte biomechanical properties differ significantly with the zone of origin, consistent with previous studies showing zonal differences in chondrocyte biosynthetic activity and gene expression. Given the versatility and dynamic testing capabilities of AFM, the ability to conduct stress-relaxation measurements using this technique may provide further insight into the viscoelastic properties of isolated cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
294
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(314 citation statements)
references
References 65 publications
12
294
2
1
Order By: Relevance
“…While there have been many mechanical property measurements of viscoelasticity in cartilage 36 , chondrons 37,38 , and chondrocytes 39,40 , this mechanotransduction study examined how the matrix viscoelasticity impacts chondrocyte behavior. Previous studies have found limited proliferation and deposition of cartilage matrix by chondrocytes encapsulated in non-degradable or slowly-degrading hydrogels of PEG 12 , agarose 13 , alginate 41 and hyaluronic acid 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been many mechanical property measurements of viscoelasticity in cartilage 36 , chondrons 37,38 , and chondrocytes 39,40 , this mechanotransduction study examined how the matrix viscoelasticity impacts chondrocyte behavior. Previous studies have found limited proliferation and deposition of cartilage matrix by chondrocytes encapsulated in non-degradable or slowly-degrading hydrogels of PEG 12 , agarose 13 , alginate 41 and hyaluronic acid 22 .…”
Section: Discussionmentioning
confidence: 99%
“…19). Similarly, cartilage, chondron, and chondrocytes have been found to exhibit viscoelastic responses with characteristic timescales ranging from 0.5 – 10 seconds 3640 . These indicate that the fast relaxing hydrogels may more closely mimic the viscoelasticity of the native cartilage microenvironment than the slow relaxing hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Despite neglecting microstructural features, continuum models enable quantifying the mechanical properties of cells under various conditions that could provide essential information of cellular subpopulations [25], disease [18], malignant transformation and cell-materials interactions [2]. However, it is worth pointing out that there is no universal mechanical model available to quantify the mechanical properties of living cells at various physiological and microenvironmental conditions, because living cells can dynamically adapt to their environment.…”
Section: Continuum Modelsmentioning
confidence: 99%
“…Zonal variations in matrix composition and structure contribute to a depth-dependent increase in compressive properties of the cartilage ECM [29 -31]. Isolated chondrocytes also demonstrate zonal differences in their mechanical properties, with superficial zone cells exhibiting higher moduli than do middle/deep zone cells [32,33]. While the three-dimensional morphology and thickness of the PCM varies among the cartilage zones [11,14], micropipette aspiration of mechanically isolated chondrons from canine [34] and human [35,36] cartilage revealed zonal uniformity in the mechanical properties of the PCM, despite significant zonal differences in ECM properties.…”
Section: Introductionmentioning
confidence: 99%